New bithiazolyl hydrazones: novel synthesis, characterization and antitubercular evaluation - Bhalerao, Mahendra B.; Dhumal, Sambhaji T.; Deshmukh, Amarsinh R.; Nawale, Laxman U.; Khedkar, Vijay M.; Sarkar, Dhiman; Mane, Ramrao A. (Bioorganic & Medicinal Chemistry Letters, 2017)
New bithiazolyl hydrazones (6a–l) have been first time synthesized by carrying novel one pot cyclocondensation of 5-acyl thiazoles (1a–b), thiosemicarbazide (2) and substituted phenacyl chlorides (4a–f) in freshly prepared ionic liquid, diisopropyl ethyl ammonium acetate (DIPEAc) at room temperature. The newly synthesized compounds have been evaluated for their antitubercular activity and the compounds 3b, 6a, 6b, 6d, 6e, 6f, 6g, and 6l have displayed noticeable antitubercular activity compared to Rifampicin with tolerable cytotoxicity. All these compounds were also screened for their antibacterial activity and found that, compounds 6j and 6k have exhibited a very good antibacterial activity. Molecular docking study has shown better harmony with the evaluation trend shown by these compounds under in vitro antitubercular screening.